Assessment of the Safety of Wild Strains of Lactobacillus as Probiotics Orogastrically Administered to Rats - Oyetayo, V. O. (Biological Sciences - PJSIR, 2005)
The safety of four wild strains of Lactobacillus, isolated from fresh cow milk and faeces of albino rat (Rattus norvegicus) was studied. Some biochemical parameters of the serum in the orogastrically-dosed rats were used as the index. A reduction in the levels of serum cholesterol and of serum aminotranferases in the rats orogastrically-dosed with Lactobacillus isolates, as compared with the control group was noted. There was no significant difference (P > 0.05) in the alkaline phosphatase levels of the control and the orogastrically-dosed rat groups. Serum globulin and bilirubin levels showed a significant difference (P < 0.05) among the control and the Lactobacillus- dosed groups. The control group recorded the highest weight gain among all the groups studied, but it was not significantly different (P > 0.05) from other treatments except in the rats dosed with the Lactabacillus casei strain isolated from cow milk. The rats dosed with Lactobacillus displayed beneficial effects as probiotics in terms of reduced serum cholesterol and liver function improvement in terms of reduction in the serum aminotransferase levels.